Complete mitochondrial genome and the phylogenetic position of the Leadhued skate Notoraja tobitukai (Rajiformes: Arhynchobatidae) - Si, Ranran (Mitochondrial DNA B Resour, 2016)
In this study, the complete mitochondrial genome of the Leadhued skate Notoraja tobitukai (Rajiformes: Arhynchobatidae) was determined. It was a circle molecular (16, 799 bp), consisted of 37 genes with a typical gene order in vertebrate mitogenome. In the whole mitogenome, there were 24 bp short intergenic and 26 bp overlaps. The nucleotide composition was 32.3% A, 22.6% C, 13.1% G and 32.0% T. Two start codons (GTG and ATG) and two stop codons (TAG, TAA/T) were used in the protein-coding genes. The 22 tRNA genes ranged from 65 bp (tRNA-Cys) to 75 bp (tRNA-Leu1). The phylogenetic result showed that N. tobitukai was clustered with the Pavoraja nitida.